A Canine's Behavior and Cognitive State as It Relates to Immobility and the Success of Physical Rehabilitation in the Non-ambulatory Spinal Cord Patient - Thomovsky, Stephanie A.; Ogata, Niwako (Frontiers in Veterinary Science, 2021)
Physical rehabilitation (PR) is recommended following spinal cord injury to help improve and maintain muscle elasticity, joint mobility and nerve health. It can also be used to relieve pain and improve cardiopulmonary fitness in an immobile patient. There is evidence, in human medicine, that PR plays a critical role in mental health and the psychological state of the patient. As part of the assessment phase, human physical therapists often identify psychosocial symptoms and barriers at the start of PR that ultimately may affect improvement in human patients suffering from injury and the loss of mobility. Patient psychological state plays an integral role in healing and outcome during treatment and rehabilitation. Specific interventions set to address these symptoms can better outcome. Arguably, one of the most emotionally traumatizing injuries suffered by a canine patient can be immobility secondary to spinal cord injury. Poorly understood is the role the canine cognitive state plays in the success of rehabilitation following spinal cord injury. Should breed, age, sex, physical fitness, personality, previous experiences and history or home lifestyle, affect the PR assessment of these patients? Do these factors affect eventual outcome following PR? The purpose of this manuscript is to explore psychosocial barriers encountered during injury rehabilitation in humans and determine if the similar barriers need to be considered when assessing a canine patient for spinal cord injury rehabilitation